Strengthening Posbindu Member in Efforts to Prevent and Control Non-Communicable Diseases (NCDs) in Gandu District, Kulon Progo, DIY - Erisa Fitria Natasari; Amalia Rahma Putri; Nisa Raudoh; Ahmad Farraz Fadel I.; Zachra Kusuma Artamevia; Berliana Febrianti; Elpina May Kasten K.; Adhitama Pangestu Ashary; Arya Adiningrat (Jurnal Pengabdian Masyarakat Bestari, 2023)
Non-communicable diseases (NCDs) are non-communicable and chronic diseases. NCDs are caused by genetic, environmental, and lifestyle factors. NCDs such as cancer and diabetes are among the highest causes of death. The implementation of Posbindu in Gandu District is currently still accompanied by Puskesmas officers. This is the focus of the Implementation Team to conduct training so that Posbindu can run independently. Posbindu training began with pre-test, material presentation, sphygmomanometer and GCU training, ended with post-test. T-Test results from pre- and post-test obtained significance values p = 0.00, sphygmomanometer training (p = 0.00), and GCU training (p = 0.00). This showed the influence of counselling and training on the knowledge and skills of PTM Posbindu member in using sphygmomanometer and GCU devices.